The Effects of Polishing Techniques on Surface Roughness of De-flex Denture Base - Ahmed Hazim Kassoob; Ihab Nafea Yaseen (Journal of Techniques)
Background: Materials are being developed to meet the needs of patients, such as flexible injectable thermoplastic resins that improve the esthetics of patients wearing removable partial dentures.